2018
DOI: 10.3802/jgo.2017.28.e87
|View full text |Cite
|
Sign up to set email alerts
|

Role of lymphadenectomy in intermediate-risk endometrial cancer: a matched-pair study

Abstract: Objective: To assess the impact of lymph node dissection (LND) on morbidity, survival, and cost for intermediate-risk endometrial cancers (IREC). Methods: A multicenter retrospective cohort of 720 women with IREC (endometrioid histology with myometrial invasion <50% and grade 3; or myometrial invasion ≥50% and grades 1-2; or cervical involvement and grades 1-2) was carried out. All patients underwent hysterectomy and bilateral salpingo-oophorectomy. A matched pair analysis identified 178 pairs (178 with LND an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…The therapeutic value of lymphadenectomy remains unclear for intermediate risk and this is partly due to the fact that previous studies were not exclusively focused on the intermediate population. To our knowledge, only Coronado et al focused on this population 22. Our results are consistent with theirs as they also demonstrated that systematic lymphadenectomy in intermediate endometrial cancer has no benefit on survival, although it does not show an increase in perioperative morbidity or global cost 22…”
Section: Discussionsupporting
confidence: 90%
“…The therapeutic value of lymphadenectomy remains unclear for intermediate risk and this is partly due to the fact that previous studies were not exclusively focused on the intermediate population. To our knowledge, only Coronado et al focused on this population 22. Our results are consistent with theirs as they also demonstrated that systematic lymphadenectomy in intermediate endometrial cancer has no benefit on survival, although it does not show an increase in perioperative morbidity or global cost 22…”
Section: Discussionsupporting
confidence: 90%